The influence of parental expectations on adolescents’ physical activity: a chain mediation model of basic psychological needs and exercise motivation - Liu, Lumin; Li, Tianpei; Long, Juan; Jin, Hwang; Ahn, Jae Woong (Frontiers in Psychology, 2025)
BackgroundAccording to the World Health Organization and UNICEF, adolescents worldwide generally engage in insufficient physical activity. Parental expectations, as a social environmental factor, are considered potentially influential on adolescent physical activity, though the specific mechanisms require further clarification.PurposeTo explore the relationships among parental expectations, basic psychological needs, exercise motivation, and adolescent sports participation, aiming to provide theoretical foundations and practical guidance for youth sports engagement in China.MethodsA survey was conducted among 1,286 school-aged adolescents in eastern, central, and western China using the Parental Expectations Scale, Basic Psychological Needs Scale, Exercise Motivation Scale, and Physical Activity Scale.ResultsParental expectations significantly and positively predicted adolescent sports participation. Basic psychological needs and exercise motivation partially mediated the relationship between parental expectations and adolescent sports participation, exhibiting a chained mediating effect.ConclusionParental expectations exert a positive influence on adolescent sports participation. Within the family context, positive expectations can translate into external motivation for youth sports engagement. The chained mediation by basic psychological needs and exercise motivation indicates that parental expectations first satisfy adolescents’ fundamental psychological needs, thereby stimulating their exercise motivation, and ultimately promoting youth sports participation.